A review. blue Wing Disease -chicken infectious anaemia molecular study - Ahmed jassim Neama; Furkan Alaraji; Aamer Rassam Ali Al-Aqaby; Israa Najm Abdullah Al-ibadi (Kufa Journal for Veterinary Medical Sciences, 2020)
Blue wing is a diseased condition of discoloured skin of wing caused mainly by Chicken anaemia virus and or reovirus. This review designed to illustrate the causative agent/s and molecular structure of the disease, epidemiology and common characters referring to pubmed as a references search tool. The disease is major cause of anaemia in chicken and the virus possess the ability to induce apoptosis in numerous chicken derived cells and tumor cell lines.